The urine Light Chain/eGFR quotient as a tool to rule out cast nephropathy in myeloma-associated kidney failure - Klank, David Karl; Löffler, Christian; Friedrich, Julian; Hoffmann, Martin; Paschka, Peter; Bergner, Raoul (Biomedicines, 2024)
Kidney involvement with resulting kidney failure leads to increased mortality in patients with multiple myeloma (MM). Cast nephropathy (CN), in particular, if left untreated, quickly leads to kidney failure requiring dialysis and has a very poor prognosis for the affected patient. The gold standard for diagnosing kidney involvement is a kidney biopsy. However, due to bleeding risk, this cannot be done in every patient. We recently reported that a quotient of urine light chain (LCurine) to glomerular filtration rate (eGFR) is a non-invasive diagnostic tool for patients with kidney involvement in MM. But this quotient has not yet been tested in everyday clinical practice. In this study, our LCurine/eGFR ratio was tested on 67 patients in two centers. Enrollment took place between January 2019 and September 2023. A total of 18 of the 67 patients had CN. With the threshold defined in our initial paper, we were able to show a sensitivity of 100% with a specificity of 85.7% for CN in patients with MM. As a result, the LCurine/eGFR quotient recognizes 100% of all CN and can therefore detect this group, which has a very poor prognosis, without the need for a kidney biopsy.